Fast multiplex bacterial PCR of bronchoalveolar lavage for antibiotic stewardship in hospitalised patients with pneumonia at risk of Gram-negative bacterial infection (Flagship II): a multicentre, randomised controlled trial. Issue 9 (September 2022) - Darie, Andrei M; Khanna, Nina; Jahn, Kathleen; Osthoff, Michael; Bassetti, Stefano; Osthoff, Mirjam; Schumann, Desiree M; Albrich, Werner C; Hirsch, Hans; Brutsche, Martin; Grize, Leticia; Tamm, Michael; et al.
Summary: Background: PCR-based testing has transformed the management of suspected respiratory viral infections. We aimed to determine whether multiplex bacterial PCR of bronchoalveolar lavage fluid aids antibiotic stewardship in patients with pneumonia. Methods: This investigator-initiated, multicentre, randomised controlled trial was conducted at two tertiary care centres in Switzerland (University Hospital of Basel and Kantonsspital St Gallen). Patients aged 18 years or older who were admitted to hospital with suspected pneumonia, had a clinical indication for bronchoscopy with bronchoalveolar lavage, and were at risk of Gram-negative bacterial infection were included. Patients were randomly assigned (1:1) to either the multiplex bacterial PCR group or the conventional microbiology control group using a random allocation sequence. Treating physicians were not masked, but the committee panel was masked to patient randomisation. All patients underwent bronchoscopy with bronchoalveolar lavage and samples were assessed by conventional microbiological culture (and additionally, in the PCR group, by multiplex bacterial PCR for Gram-negative rods using the Unyvero Hospitalized Pneumonia [HPN] Cartridge; Curetis, Holzgerlingen, Germany). Patients received empirical antibiotic therapy as clinically indicated by the treating physician. In the PCR group, a recommendation regarding antibiotic therapy was made approximately 5 h after taking the sample. The primary outcome was the time in hours on inappropriate antibiotic therapy from bronchoscopy to discharge or to 30 days after bronchoscopy. This trial was registered with the International Clinical Trials Registry Platform, ISRCTN95828556. Findings: Between May 31, 2017, and Sept 25, 2019, 740 patients with pneumonia were screened for eligibility and 208 were included and randomly assigned to the PCR group (n=100) or conventional microbiology control group (n=108). The mean age of patients was 65·9 years (SD 14·0) and 135 (65%) were male. After daily follow-up until hospital discharge or for a maximum of 30 days, the duration of inappropriate antibiotic treatment was significantly shorter by 38·6 h (95% CI 19·5–57·7) in the PCR group than in the control group (adjusted mean 47·1 h [34·7–59·5] vs 85·7 h [78·8–95·6]; p<0·0001), which translates as a decrease in the duration of inappropriate antibiotic therapy of 45·0% (37·9–52·1). Adverse events due to antimicrobial therapy occurred in nine patients (five [5%] in the PCR group vs four [4%] in the control group) and due to bronchoscopy occurred in four patients (two [1%] vs two [1%]). There were eight (8%) deaths in the PCR group and 11 (10%) in the control group. All in-hospital deaths were attributed to a respiratory cause. Interpretation: Multiplex bacterial PCR examination of bronchoalveolar lavage decreases the duration of inappropriate antibiotic therapy of patients admitted to hospital with pneumonia and at risk of Gram-negative rod infection. This approach warrants further consideration in future antibiotic stewardship strategies. Funding: Curetis and the Clinic of Respiratory Medicine and Pulmonary Cell Research, University Hospital Basel, Switzerland.